Liquidity and Leverage Effects on Profitability: Evidence from PT Link Net Tbk (2015–2024) - Piay, Rehelia Yemima; Bachtiar, Ardi (Indonesian Financial Review, 2025)
This study explores the influence of Current Ratio (CR) and Debt to Asset Ratio (DAR) on Return on Assets (ROA) at PT Link Net Tbk from 2015 to 2024 using a quantitative approach. The research analyzes the company’s financial statements as both population and sample. Findings indicate that CR does not significantly affect ROA, whereas DAR has a negative and significant impact. When examined together, CR and DAR significantly influence ROA. The results suggest that liquidity alone does not determine profitability, while leverage plays a critical role in asset returns. These insights emphasize the importance of prudent debt management and financial planning for improving company performance, offering guidance for management in optimizing financial structure to enhance overall profitability.